IMPLEMENTATION OF SUPERVISION AND SELF-EVALUATION OF SCHOOLS WITH PERFORMANCE OF TEACHERS (Journal of Namibian Studies : History Politics Culture, 2023)
Supervision and evaluation of school principals is an important thing that must be improved so that teacher performance becomes even better. Therefore, this thesis discusses the relationship between the implementation of school supervision and self-evaluation with teacher performance at Junior High School of Serang city. The research was conducted with the aim of knowing the relationship between the implementation of supervision and school self-evaluation with teacher performance. To achieve this goal, descriptive analysis is used. The study was conducted on state teachers of Junior High School in Serang city with a sample of 69 of the 221 population. Furthermore, to analyze the relationship between variables, a quantitative approach is used and a descriptive correlation design is used. The results showed (1) There was a significant relationship between the implementation of supervision and teacher performance of 5.386 with indicators of implementation, targeting, application of principles, use of techniques, follow-p plans for supervision, as well as rewards and warnings; (2) There is a significant relationship between school self-evaluation on teacher performance of 8,295 with indicators of planning, school development and school-based management; (3) The implementation of school supervision and self-evaluation is significantly related to teacher performance by 72% with teacher performance indicators of professional competence, pedagogic competence, social competence, and personality competence.